PERBEDAAN MOTIVASI MENYELESAIKAN SKRIPSI ANTARA MAHASISWA YANG BEKERJA DENGAN MAHASISWA YANG TIDAK BEKERJA - Dudija, Nidya (HUMANITAS (Jurnal Psikologi Indonesia), 2011)
This study aims to examine whether there is difference in motivation tocomplete a thesis between employed students with unemployed students.Motivation to complete a thesis scale was used to get the data. T-test wasused to analysis data.Â  The result of t-test confirmed that there is a significant difference in motivation to complete thesis between employed student with unemployed student (t= 4.085) with p= 0.000 < 0.05).Â  Employed student had higher motivation than unemployed student in completion their thesis. This result will be discussed further.